Wide field of view large aperture meta-doublet eyepiece - Anna Wirth-Singh; Johannes E. Fröch; Fan Yang; Louis Martin; Hanyu Zheng; Hualiang Zhang; Quentin T. Tanguy; Zhihao Zhou; Luocheng Huang; Demis D. John; Biljana Stamenic; Juejun Hu; et al. (Light: Science & Applications)
Abstract Wide field of view and light weight optics are critical for advanced eyewear, with applications in augmented/virtual reality and night vision. Conventional refractive lenses are often stacked to correct aberrations at a wide field of view, leading to limited performance and increased size and weight. In particular, simultaneously achieving a wide field of view and large aperture for light collection is desirable but challenging to realize in a compact form-factor. Here, we demonstrate a wide field of view (greater than 60∘) meta-optic doublet eyepiece with an entrance aperture of 2.1 cm. At the design wavelength of 633 nm, the meta-optic doublet achieves comparable performance to a refractive lens-based eyepiece system. This meta-doublet eyepiece illustrates the potential for meta-optics to play an important role in the development of high-quality monochrome near-eye displays and night vision systems.